2010
DOI: 10.1590/s1807-59322010001100003
|View full text |Cite
|
Sign up to set email alerts
|

The association between estimated average glucose levels and fasting plasma glucose levels

Abstract: OBJECTIVE:The level of hemoglobin A1c (HbA1c), also known as glycated hemoglobin, determines how well a patient's blood glucose level has been controlled over the previous 8–12 weeks. HbA1c levels help patients and doctors understand whether a particular diabetes treatment is working and whether adjustments need to be made to the treatment. Because the HbA1c level is a marker of blood glucose for the previous 60–90 days, average blood glucose levels can be estimated using HbA1c levels. Our aim in the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 14 publications
2
46
0
Order By: Relevance
“…An examination of the biomedical parameters of the diabetes subjects in this study showed that there were no statistical differences in the glycemic characteristics of FPG, OGTT, and HbA1c between the male and female groups. In line with the results of this study, studies in Turkey, in patients at a high risk for diabetes in the US, and in cynomolgus monkeys with impaired FPG, indicate that sex is not associated with FPG level [12][13][14]. Another study on diabetic and nondiabetic subjects showed significant differences in FPG level between males and females [15].…”
Section: Discussionsupporting
confidence: 86%
“…An examination of the biomedical parameters of the diabetes subjects in this study showed that there were no statistical differences in the glycemic characteristics of FPG, OGTT, and HbA1c between the male and female groups. In line with the results of this study, studies in Turkey, in patients at a high risk for diabetes in the US, and in cynomolgus monkeys with impaired FPG, indicate that sex is not associated with FPG level [12][13][14]. Another study on diabetic and nondiabetic subjects showed significant differences in FPG level between males and females [15].…”
Section: Discussionsupporting
confidence: 86%
“…Our meta-analysis showed a significant reduction in HbA1c following N. sativa consumption. As HbA1c reflects average glucose in the past 90 days (Bozkaya, Ozgu, & Karaca, 2010), we performed additional subgroup analysis according to trial duration (<90 days and ≥90 days). Subgroup analysis revealed that HbA1c was significantly reduced in trials with <90 days length, whereas a borderline significant reduction was found in the studies with ≥90 days length.…”
Section: Discussionmentioning
confidence: 99%
“…Validation of the physiological relevance of the PCs is important, but challenging, since few studies provide gold standard measurements of metabolic features in combination with FDA of OGTT. In non-pregnant populations, high correlations between HbA1c and FG and 2hG have been found (34,35). It may therefore be speculated that the information in average measurements like the HbA1c may partly overlap with the information in the PC1 scores.…”
Section: Discussionmentioning
confidence: 99%